Pengetahuan Tentang Kehamilan, Dukungan Keluarga dan Kecemasan Ibu Primigravida Trimester III - Hernanto, Fauziah F (Persona:Jurnal Psikologi Indonesia, 2016)
The purpose of this researchwas to determine the relationship between knowledge aboutpregnancy and family support with anxiety in primigravida (first pregnancy) in facing labor.Themethod used in this research is the quantitative approach. Data is collected using questionnaires,regression analysis using a sample of 54 third trimester pregnant primigravida womens who carryout checks on Private Midwives Practices belong Vivi Umamiyanto, at Jl. Jambangan Surabaya.Theresults of the partial regression analysis between knowledge of pregnancy with anxiety showed at t= 0.715 p = 0.478 (p> 0.05), which means there is no significant relationship, as well as the resultof family support with anxiety showed t = 0.188 to p = 0.851 (p> 0.05), which means there is nosignificant relationship. The study also showed that simultaneous regression analysis coefficientshowed F = 0.315 p = 0.731 (p> 0.05) meaning that there are no significant relationship betweenknowledge about pregnancy and family support with anxiety. Effective contribution amounted toonly 1.2%. Meaning there is no significant relationship between the knowledge of pregnant womenabout pregnancy and family support with anxiety.It can be concluded that the results of regressionanalysis showed that there was no relationship between knowledge about pregnancy and familysupport with the anxiety of pregnant women. For further researchers is expected to select anothervariables are possible correlation with maternal anxiety in the face of labor.Keywords : Knowledge of Pregnancy, Family Support, Pregnancy Anxiety